Pelesapan Subjek Kalimat Majemuk dalam Bahasa Melayu-Manado - Amelia Cindy Mogi (Varied Knowledge Journal, 2026)
Ellipsis is a language syntactical phenomenon where a word or some words and phrases are omitted for the sake of sentence efficiency. Words that had gone through ellipsis are reversible and can still be retrieved or recovered without changing the sentence’s overall meaning. Subject ellipsis is quite a common topic discussed in linguistics, especially for pro-drop languages. This study investigates the ellipsis phenomenon for Malay-Manadonese words, particularly subject ellipsis based on the results of other languages’ subject ellipsis such as, Indonesian and English. The research is designed using qualitative descriptive method to explain this phenomenon thoroughly. The data were compiled from Malay-Manadonese utterances in three social media accounts and were analyzed using Sudaryanto’s Agih (Distribution) technique, circling around data expansion. This was used to verify whether the sentence data had indeed undergone subject ellipsis which is characterized by no change of meaning after the subjects are restored. The results of the research found that, similar with the other languages, Malay-Manadonese has three types of subject ellipsis: the null subject ellipsis, coordinative compound ellipsis, and subordinative compound ellipsis.